Letter - Rhymney And Abertysswg Trades and Labour Council, 11 May 1926 (Rhymney)
1926-05-11 "Letter - Rhymney And Abertysswg Trades and Labour Council, 11 May 1926" [g0167001.jpg], 11 May 1926, Rhymeny And Abertysswg Trades and Labour Council Local Organisation